Snowy Owl nest failures caused by blackfly attacks on incubating females - Solheim, Roar; Jacobsen, Karl-Otto; Øien, Ingar Jostein; Aarvak, Tomas; Polojärvi, Petteri (Ornis Norvegica, 2013)
Blackflies (Simuliidae) have been shown to influence birds negatively in several ways. In 2011, during a peak lemming year, we found that two of 28 nests of Snowy Owls Bubo scandiacus in Northern Norway and Finland failed due to blackfly attacks on the incubating female. The observations also suggest that adult survival may be influenced by these insects. The owls’ choice of breeding habitat can be decisive in their vulnerability to blackflies.